2022
DOI: 10.1002/ppul.26165
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of pulmonary involvement in children with COVID‐19: How strongly associated is viral load?

Abstract: The purpose of this study was to identify risk factors for pulmonary involvement by examining the demographic, clinical, and laboratory characteristics of children with COVID‐19. We performed a retrospective single‐center study of COVID‐19 in children treated at a tertiary care hospital in Turkey from December 2020 to June 2021. During the course of the study, 126 patients were evaluated, of whom 70/126 were male. The patients' ages ranged from 1 to 216 (mean, 4.73 ± 81.11) months. Fever (65.9%), cough (52.4%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that low lymphocyte counts are associated with poor prognosis in acute and chronic inflammatory conditions such as sepsis, cancer, and cardiovascular and pulmonary diseases [ 22 24 ]. However, it has not yet fully understood how low lymphocyte causes immune system abnormalities in patients with pediatric UTI and increases bacteremia [ 25 , 26 ]. Therefore, further research is needed on these mechanisms and cutoff values of lymphocyte levels to predict bacteremia in young infants with febrile UTI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that low lymphocyte counts are associated with poor prognosis in acute and chronic inflammatory conditions such as sepsis, cancer, and cardiovascular and pulmonary diseases [ 22 24 ]. However, it has not yet fully understood how low lymphocyte causes immune system abnormalities in patients with pediatric UTI and increases bacteremia [ 25 , 26 ]. Therefore, further research is needed on these mechanisms and cutoff values of lymphocyte levels to predict bacteremia in young infants with febrile UTI.…”
Section: Discussionmentioning
confidence: 99%